PENGEMBANGAN BAHAN AJAR KALKULUS INTEGRAL BERBASIS ANIMASI - Ali Shodikin (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
Learning integral calculus should be done with interesting and fun process, because this course is basic materials and a prerequisite for other subjects as well as the provision of teaching materials for high school students. However, based on the documentation that have done in one of the private universities in Lamongan in the last two years shows that the average score of student results in mathematics education and mathematics subjects integral calculus has only reached 42%. This suggests that the results of student learning especially integral calculus courses still low. One effort that can be done is to develop teaching materials based animation. Media animation that comes with the animations, audio, and video in teaching and learning can grow the interest of learners. Based on these descriptions, this study aims to develop teaching materials integral calculus-based animation. This study uses a study design development consists of four stages, namely: (1) definition, (2) design, (3) development, and (4) dissemination. The end product of this research is animation-based teaching media for the course of integral calculus.